Peran Guru Rupaka Dalam Menguatkan Sradha Dan Bakti Anak Melalui Guna Melalui Pendidikan Informal Di Wilayah Jakarta Timur - Made Anggara; I Wayan Budha; I Ketut Angga Irawan; I Made Awanita (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2023)
Children are the younger generation of Hindus who are aware of their obligations as shoots, the forerunner to successors, keepers, builders and developers of dharma teachings. This means that every child or youth has the same duties and responsibilities in carrying out the teachings of dharma. No need on a large scale, just enough in simple things first. One of them is proud to be a Hindu child and still Hindu. Thus this thesis discusses the Role of Guru Rupaka in Strengthening Sradha and Bakti To Strengthen the Existence of Hinduism Through Informal Education in East Jakarta Region. The purpose of this study is why it is necessary to strengthen sradha and devotion to strengthen the existence of Hinduism through Informal Education in East Jakarta and how the efforts made by Guru Rupaka in Strengthening Sradha and Bakti In order to strengthen Hinduism through Informal Education in East Jakarta. This research is a qualitative research with a descriptive design.Data collection techniques use interviews, observation, and documentation. The author conducted interviews with informants consisting of people of the Ummah, and one key informant to obtain in-depth information. The author collected data approximately 4 months in the Field. The results of the study prove that every parent in carrying out a married life certainly has a very important task and role, there are also tasks and roles of parents towards their children can be stated as follows: giving birth, caring, raising, leading to maturity and instilling norms and applicable values. Besides that, it must also be able to develop the potential that exists in children, set an example and be able to develop personal growth with full responsibility and compassion.